2007
DOI: 10.1016/j.physc.2007.03.361
|View full text |Cite
|
Sign up to set email alerts
|

Origin of strong coupling in lithium under pressure

Abstract: In an attempt to provide a clearer understanding of the impressive increase in Tc under pressure in elemental Li, linear response calculation of the phonon dispersion curves, electron-phonon matrix elements, phonon linewidths and mode λ's have been carried out on a finer mesh (24 3 in the Brillouin zone) than done previously, for the volume corresponding to 20 GPa pressure. The result illustrates the great need for a fine mesh (even finer than this) for converged results of λ and the spectral function α 2 F . … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The report by Drozdov, Eremets, and Troyan 1 (DET) of superconductivity up to T c =190 K in H 2 S compressed to the 200 GPa regime has reignited excitement in the possibility of achieving room temperature superconductivity. This report builds on previous success of pressure enhancement of T c in a variety of types of materials: from 134K to 164K in the cuprate Hg2223, 2,3 from zero to 20-25 K in the simple metals Li, Ca, and Y, [4][5][6][7][8][9][10] and from zero to 14K in the insulator silicon. 11 An anticipated major factor is the increase in the phonon energy scale with compression, since it sets the temperature scale for T c , as pointed out early on 12 and reviewed more recently 13 by Ashcroft in predicting possible room temperature superconductivity in metallic hydrogen.…”
supporting
confidence: 64%
“…The report by Drozdov, Eremets, and Troyan 1 (DET) of superconductivity up to T c =190 K in H 2 S compressed to the 200 GPa regime has reignited excitement in the possibility of achieving room temperature superconductivity. This report builds on previous success of pressure enhancement of T c in a variety of types of materials: from 134K to 164K in the cuprate Hg2223, 2,3 from zero to 20-25 K in the simple metals Li, Ca, and Y, [4][5][6][7][8][9][10] and from zero to 14K in the insulator silicon. 11 An anticipated major factor is the increase in the phonon energy scale with compression, since it sets the temperature scale for T c , as pointed out early on 12 and reviewed more recently 13 by Ashcroft in predicting possible room temperature superconductivity in metallic hydrogen.…”
supporting
confidence: 64%
“…15,16 In previous electron-phonon reports it has been suggested that a very fine BZ sampling is necessary to calculate the total coupling parameters in pressurized Li with high precision. [15][16][17][18] Interestingly, studies under extreme pressures indicate that the electronic structure of Li evolves into a paired insulating state which gives an upper limit to the pressure at which superconductivity may be observed. 10,19 In this paper we study the pressure evolution of the total electron-phonon coupling for the monatomic fcc phase of Li in the 8-36 GPa range.…”
Section: Introductionmentioning
confidence: 99%
“…Another example is lithium, whose transition temperature is less than 0.4mK at ambient pressure [35] and as high as 20K under pressure [36]. Phonon properties of lithium under pressure were studied by Kasinathan, Koepernik, Kunes, Rosner and Pickett in 2007 [37]. We may gain very interesting insight into lithium as a superconductor once α 2 F (ν) of the metal is measured.…”
Section: Discussionmentioning
confidence: 99%